Childhood cerebral visual impairment subtype classification based on an extensive versus a limited test battery - Philip, Jannet; Huurneman, Bianca; Jansonius, Nomdo M.; Cillessen, Antonius H. N.; Boonstra, Frouke N. (Frontiers in Neuroscience, 2023)
To classify CVI subtypes and compare the added value of an extensive test battery over a limited test battery in subtype classification of cerebral visual impairment(CVI)in children. Methods:Seventy-five children with a clinical diagnosis of CVI(median[IQR] age:9 [7-12] years) were identified from the medical records. The extensive test battery included visual acuity,contrast sensitivity, ocular alignment, eye movement analysis, visual field analysis, optic nerve head evaluation, and evaluation of visual perception. The limited test battery included visual acuity, contrast sensitivity, ocular alignment, and evaluation of visual perception. Principal component analysis(PCA)followed by cluster analysis was done, for both test batteries separately, to determine the optimum subtype classification for CVI.Results: Fifty-one participants with an extensive test battery with mild to moderate visual impairment were included in the main analysis.This resulted in four CVI subtypes for the extensive test battery (subtle characteristics, higher-level visual function deficits, lower-level visual function deficits, and higher-and lower-level visual function deficits)and three CVI subtypes for the limited test battery(subtle characteristics, higher-level visual function deficits, and higher-and lower-level visual function deficits).There were significant differences between the subtypes for 9 out of 10 measures of the extensive and all 4 measures of the limited test battery(p<0.05).The subtle characteristics subtype(extensive n=19, limited n=15)showed near normal lower and higher-level visual functions in both test batteries. The higher-level visual function deficits subtype (extensive n=18, limited n=24)showed near normal visual acuity combined with significant visual perceptual deficits in both test batteries; accompanied by visual pathways defects and abnormal eye movement behaviour in the extensive test battery. The higher-and lower-level visual function deficits subtype(extensive n=4, limited n=12)showed both higher and lower-level visual function deficits in both test batteries, but application of the extensive test battery revealed additional visual pathways defects and abnormal eye movement behavior. The lower-level visual function deficits CVI subtype(extensive n=10)was a new subtype identified by the extensive test battery.This subtype showed lower-level visual function deficits together with abnormal eye movement measures.Conclusion:Comparison of the two test batteries revealed the added value of an extensive test battery in classifying CVI.The outcomes of this study, therefore, have provided a new direction in the area of CVI classification.